Aggressors and resilient youths in Medellin, Colombia: the need for a paradigm shift in order to overcome violence (2013)
ABSTRACT: The objective of this study was to estimate the ratio of resilient youth and compare this to youth with aggressive behavior, and to youth who also exhibit sexually risky behavior and drug use. A cross-section study of a representative sample of people between aged between 12 and 60 who are residents of Medellin, Colombia, and its metropolitan area (N = 4,654) was employed using probabilistic multi-stage sampling. Youth between 14 and 26 years old were selected for the present analysis (n = 1,780). The proportion of resilient youth is 22.9%, of aggressors is 11.3%, and that of youth with other risky conduct is 65.8%. The high ratio of resilient youth calls for a reorientation of public policy toward prevention and control of violence, prioritizing the promotion of resilient behavior instead of continuing with tertiary prevention actions.